2021
DOI: 10.1016/j.xcrm.2021.100228
|View full text |Cite
|
Sign up to set email alerts
|

Long-term persistence of RBD+ memory B cells encoding neutralizing antibodies in SARS-CoV-2 infection

Abstract: Considerable concerns relating to the duration of protective immunity against SARS-CoV-2 exist, with evidence of antibody titres declining rapidly after infection and reports of reinfection. Here we monitor the antibody responses against SARS-CoV-2 receptor binding domain (RBD) for up to six months after infection. While antibody titres are maintained, about 13% of the cohort’s neutralising responses return to background. However, encouragingly in a selected subset of 13 participants, 12 have detectable RBD-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
88
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(95 citation statements)
references
References 46 publications
7
88
0
Order By: Relevance
“…Previous acute phase studies showed that COVID-19 severity was associated with higher antibody responses. Here, hospitalization was associated with higher immunoglobulin levels many months after convalescence, suggesting that severity does not affect stability of memory B cell and plasma cells producing antibodies [ 2 4 , 19 ]. Common symptoms like fever and highly specific symptoms like alteration in smell and taste were also associated with higher antibodies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous acute phase studies showed that COVID-19 severity was associated with higher antibody responses. Here, hospitalization was associated with higher immunoglobulin levels many months after convalescence, suggesting that severity does not affect stability of memory B cell and plasma cells producing antibodies [ 2 4 , 19 ]. Common symptoms like fever and highly specific symptoms like alteration in smell and taste were also associated with higher antibodies.…”
Section: Resultsmentioning
confidence: 99%
“…Diversity in epitope specificity, quality, and functional capacity of antibodies will likely affect the efficacy of the immunity mediated. Antibodies elicited after exposure to SARS-CoV-2 have been associated with protective immunity up to 6 months [ 2 – 5 ], although we do not yet have a correlate of protection, and reinfections occur seemingly at a low frequency. The spike (S) protein on the virus surface is considered the main target of protective antibodies and the component of the leading vaccines [ 6 ] already under implementation.…”
Section: Introductionmentioning
confidence: 89%
“…Spike-specific IgG antibodies and virus-specific memory T cells may decrease with time, but virus-specific memory B-cells increase. 12…”
Section: Figurementioning
confidence: 99%
“…A recent study confirmed that SARS-CoV-2 infection induces long-lived bone marrow plasma cells [493]. Thus, waning nAb titers in plasma several months post infection may be compensated by the persistent Bmem repertoire that remains at constant levels or can even increase [494]. Further studies are required to elucidate the contribution and protective capacity of Bmem cells in SARS-CoV-2 infection.…”
Section: B Cellsmentioning
confidence: 91%